Translation practices in cross-cultural social research and guidelines for the most popular approach: back-translation - Kowal, Marta (Anthropological Review, 2024)
In recent years, there has been a notable increase in the number of cross-cultural research, marking a positive shift from the predominantly WEIRD (Western, Educated, Industrialized, Rich, and Democratic) scientific focus. Most people are not WEIRD, and thus, such a trend is widely appraised. However, cross-cultural research bears many risks, one of which is a language barrier. Conducting studies in various populations that communicate in different languages results in the need to translate the study materials. A proper translation is essential for ensuring the validity and reliability of the data. This study aims to discuss translational practices in cross-cultural research, based on the analysis of studies published between 2017 and 2021 in two respected in cross-cultural social research journals (i.e., Cross-Cultural Research and Journal of Cross-Cultural Psychology). The results revealed that one fifth of the analyzed studies lacked crucial information regarding translation procedures. Among the studies that did report on translation methods, back-translation was the most popular approach, with nearly half of the studies utilizing this technique. The recommendations for cross-cultural researchers are outlined, with an emphasis on the sufficient description of the samples, including their nationality and used language. In addition, guidelines for the back-translation are reiterated: 1) forward and 2) back translation, 3) versions’ comparison, 4) pilot study, and 5) revision of the final version.